2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626483
|View full text |Cite
|
Sign up to set email alerts
|

Spike detection in extracellular recordings by hybrid blind beamforming

Abstract: In the case of extracellular recordings, spike detection algorithms are necessary in order to retrieve information about neuronal activity form the data. We present a new spike detection algorithm which is based on methods from the field of blind equalization and beamforming. In contrast to existing approaches, our method estimates several waveforms directly from the data and corresponding linear filters are constructed. The estimation is done in an unsupervised manner, and the few parameters of the algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Because we use techniques from both fields, that is, blind equalization and classical beamforming, in the context of spike detection, we call our method hybrid blind beamforming for spike detection (HBBSD). A simplified version of the core algorithm and some preliminary results were published in [25]. This contribution not only extends both in several ways but also presents a significant amount of new algorithms and results.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Because we use techniques from both fields, that is, blind equalization and classical beamforming, in the context of spike detection, we call our method hybrid blind beamforming for spike detection (HBBSD). A simplified version of the core algorithm and some preliminary results were published in [25]. This contribution not only extends both in several ways but also presents a significant amount of new algorithms and results.…”
Section: Introductionmentioning
confidence: 88%
“…In [25] we compared the performance of HBBSD with existing methods covering all categories described in Section 1. It was demonstrated that, in general, algorithms relying on waveform information outperform methods which are solely based on amplitude thresholding or transient detection.…”
Section: Competing Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This either requires knowledge of the spike's waveform or generic approaches to find suitable templates. Such algorithms are described for example in [8,9,15,17].…”
Section: B Template Based Correlationmentioning
confidence: 99%
“…Several algorithms for spike detection have already been published [1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Based on their methodological concept most of them can be divided into three categories (as suggested in [1]):…”
Section: Introductionmentioning
confidence: 99%